Increased Liver Uptake and Reduced Hepatic Stellate Cell Activation with a Cell-Specific Conjugate of the Rho-kinase Inhibitor Y27632 - van Beuge, Marike Marjolijn (Springer US, 2011)
PURPOSE: Rho-kinase regulates activation of hepatic stellate cells (HSC) during liver fibrosis, but the ubiquitous presence of this kinase may hinder examination of its exact role and the therapeutic use of inhibitors. We therefore coupled the Rho-kinase inhibitor Y27632 to a drug carrier that binds the mannose-6-phosphate insulin-like growth factor II (M6P/IGFII)-receptor which is upregulated on activated HSC. METHODS: Y27632 was coupled to mannose-6-phosphate human serum albumin (M6PHSA), and in vitro experiments were performed on primary rat HSC. Biodistribution and effect studies were performed in an acute CCl(4) model in mice. RESULTS: Y27-conjugate remained stable in serum, while drug was efficiently released in liver homogenates. Receptor-blocking studies revealed that it was specifically taken up through the M6P/IGFII-receptor on fibroblasts, and it inhibited expression of fibrotic markers in activated HSC. In vivo, liver drug levels were significantly higher after injection of Y27-conjugate as compared to Y27632, and the conjugate accumulated specifically in HSC. After acute CCl(4)-induced liver injury, Y27-conjugate reduced the local activation of HSC, whereas an equimolar dose of free drug did not. CONCLUSIONS: We conclude that specific targeting of a Rho-kinase inhibitor to HSC leads to enhanced accumulation of the drug in HSC, reducing early fibrogenesis in the liver. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11095-011-0430-9) contains supplementary material, which is available to authorized users.